2021
DOI: 10.5021/ad.2021.33.1.61
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale, Stratified Genetic Analysis of the Major Histocompatibility Complex Region in Early- and Late-Onset Psoriasis in China

Abstract: Background Psoriasis vulgaris is a chronic inflammatory skin disease which occur at any age. It can be clinically classified into two age-onset subtypes: early-onset psoriasis (EOP; <40 years) and late-onset psoriasis (LOP; ≥40 years). More evidence showed EOP and LOP have different genetic architecture, notably the risk allele human leukocyte antigen (HLA)-C * 06:02 located within the major histocompatibility complex (MHC) region, which was reported to be the outstandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…To evaluate the levels of serum lipids in patients with psoriasis with different phenotypes and the change after MTX treatment, we first characterized the serum lipid profiles of 96 patients with psoriasis and further identified the differentially expressed lipids between EOP and LOP. Some previous studies have shown that EOP and LOP differ in their clinical characteristics and genetic background [ 5 , 17 , 18 ]. By comparing the serum lipid metabolites in LOP and EOP, we found that the levels of DG (16: 1/18: 1) and DG (18: 1/18: 1) significantly increased in EOP.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the levels of serum lipids in patients with psoriasis with different phenotypes and the change after MTX treatment, we first characterized the serum lipid profiles of 96 patients with psoriasis and further identified the differentially expressed lipids between EOP and LOP. Some previous studies have shown that EOP and LOP differ in their clinical characteristics and genetic background [ 5 , 17 , 18 ]. By comparing the serum lipid metabolites in LOP and EOP, we found that the levels of DG (16: 1/18: 1) and DG (18: 1/18: 1) significantly increased in EOP.…”
Section: Discussionmentioning
confidence: 99%
“…Also, HLA-Cw6 positivity is known to be related to stress, obesity 6 , and guttate psoriasis 7 . In addition, patients carrying the allele are more likely to have arm, leg, and trunk involvement, along with the Koebner phenomenon 8 . Several studies involving Caucasian and Chinese patients have shown HLA-Cw6-positive patients to be more responsive to methotrexate 9 and ustekinumab 6 10 11 12 ; HLA-Cw6 positivity also tends to be less frequent in high-need patients, who fail conventional therapy 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis in PsO patients confirmed that HLA alleles explain a larger heritability of EOP, moving towards a genetic profiling to predict the PsO risk of a more severe phenotype [ 5 ]. The PsO stratification age among PsA patients was also assessed, showing that it could play a role in the clinical and genetic features of PsA patients [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%